2017
DOI: 10.1111/1348-0421.12497
|View full text |Cite
|
Sign up to set email alerts
|

EDIII‐DENV3 nanospheres drive immature dendritic cells into a mature phenotype in an in vitro model

Abstract: Domain III of E protein of dengue virus (DENV) is a target for vaccine development. Unfortunately, this protein based platform has low general immunogenicity. To circumvent this problem, the use of an adjuvant-nanoparticle delivery system to facilitate immunogenicity of soluble DENV-EDIII protein was investigated. One of the key features of this delivery system is its ability to simultaneously deliver antigens and exert adjuvanticity on specialized immune cells. In this study, N-trimethyl chitosan (TMC) nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Treatment with empty TMC nPs also up-regulated expression of maturation markers at significantly higher levels than medium-treated cells. Previous studies showed that TMC nPs were able to stimulate DC maturation [ 24 , 71 ]. Accordingly, it might be possible that these act synergistically to induce MoDCs maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with empty TMC nPs also up-regulated expression of maturation markers at significantly higher levels than medium-treated cells. Previous studies showed that TMC nPs were able to stimulate DC maturation [ 24 , 71 ]. Accordingly, it might be possible that these act synergistically to induce MoDCs maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The EE and LE of the nanospheres were determined (Yang et al, 2017). The nanospheres were characterized using FTIR (Abbas et al, 2018;Dong et al, 2018), electron microscopy (Shi et al, 2016;Nantachit et al, 2017;Tao et al, 2018), and laser particle size analysis (Couvreur et al, 2002;Zhang et al, 2015;Shi et al, 2016;Ahmad et al, 2018;Panchu et al, 2018;von Halling Laier et al, 2018). The results showed that C-PC/CMC-CD55sp nanospheres were successfully constructed.…”
Section: Discussionmentioning
confidence: 99%
“…Encapsulation Efficiency (EE) and Loading Efficiency (LE) of C-PC in nanospheres were calculated as follows (Yang et al, 2017): EE = weight of C − PC in the nanospheres initial weight of C − PC  100 % LE = weight of C − PC in the nanospheres weight of the nanospheres  100 % Nanospheres were evaluated using FTIR spectra across the range of 500-4,000 cm -1 (Abbas et al, 2018;Dong et al, 2018). Nanospheres morphology was observed using a transmission electron microscope (Shi et al, 2016;Nantachit et al, 2017;Tao et al, 2018). Zeta potential (surface charge) and particle size (nanospheres size) were measured using a laser particle size analyzer at 25°C (Zhang et al, 2015;Ahmad et al, 2018;Panchu et al, 2018;von Halling Laier et al, 2018).…”
Section: Synthesis Of C-pc/cmc-cd55sp Nanospheresmentioning
confidence: 99%
“…Overall, in vitro models have proved to be a useful tool to study MBF, with examples that study virus molecular mechanisms (Correa et al, 2015; Londono-Renteria et al, 2017; Rattanamahaphoom et al, 2017), their implication in the inflammatory response (Lim et al, 2014; Duran et al, 2016), drug screening (Stolp et al, 2015; Wang L. F. et al, 2015; Sayce et al, 2016), or vaccine development (Nantachit et al, 2016, 2017; Kam et al, 2017). Thus, human cell-derived in vitro models could present a solution to modeling MBF infection and neuropathogenesis.…”
Section: In Vitro Studiesmentioning
confidence: 99%